Sustainable exploitation of mafic rock quarry waste for carbon sequestration following ball milling. (December 2018) - Rigopoulos, Ioannis; Török, Ákos; Kyratsi, Theodora; Delimitis, Andreas; Ioannou, Ioannis
Abstract: Mineral carbonation has been proposed as a safe method for carbon capture and storage (CCS). Mafic lithologies are among the most promising rocks for mineral carbonation due to their high content in Ca, Fe and Mg-bearing silicate minerals, which react with CO2 to form stable carbonate phases. Here, we discuss the potential of using waste material from mafic rock quarries for CCS, following the ball milling process. In contrast with other mineral carbonation strategies, the proposed use of quarry fines (<75 µm) could eliminate some of the cost associated with the extraction and grinding of the source material, making the whole methodology more economically and technologically viable. Potential applications include the use of ball-milled mafic rock quarry fines (i) as feedstock for ex situ mineral carbonation, and (ii) as nano-additives in replacement to the binder, for the production of environmentally-friendly building materials with potential ability to sequester CO2 . Both applications could substantially contribute to the mitigation of atmospheric CO2 concentrations over the next few decades, as well as to the upturn of the quarrying industry in many European countries that have abundant mafic lithologies, such as in Cyprus and Hungary. Graphical abstract: fx1 Highlights: Mafic rock quarry wastes (MRQW) can be used for carbon sequestration applications. Ball milling can substantially enhance the CO2 sequestration capacity of MRQW. Milled MRQW could be used as feedstock of an ex situ mineral carbonation route. Milled MRQW could be used for the production of eco-friendly building materials. This approach could lead to great environmental and economic advantages.